Therapeutic effects of whole-body vibration on fracture healing in ovariectomized rats: a systematic review and meta-analysis. Issue 6 (June 2019) - Chen, Jinman; Ruan, Hongfeng; Liu, Yang; Bao, Jiamin; Xu, Hao; Yao, Min; Cui, Xuejun; Liang, Qianqian; Wang, Yongjun
Abstract: Objective: Whole-body vibration (WBV), providing cyclic mechanical stimulation, has been used to accelerate fracture healing in preclinical studies. This study aimed to summarize and evaluate the effects of WBV on bone healing in ovariectomized rat models and then analyze its potential effects on fractures in human postmenopausal osteoporosis. Methods: PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, VIP, SinoMed, and WanFang databases were searched from their inception date to September 2017, and an updated search was conducted in January 2018. Studies that evaluated the effects of WBV on bone healing compared with control groups in ovariectomized rats were included. Two authors selected studies, extracted data, and assessed the methodological quality. Meta-analyses were performed when the same outcomes were reported in two or more studies. Results: Nine eligible studies were selected. In treatment groups, callus areas were significantly improved in the first 3 weeks, normalized total bone volume and total tissue volume values increased dramatically at 8 weeks, and the mechanical tests showed a significant difference at the end point of the study. Conclusions: This study suggested that WBV could accelerate callus formation in the early phase of bone healing, promote callus mineralization and maturity in the later phase, and restore mechanical properties of bones. Abstract : Supplemental Digital Content is available in the text